Pengaruh Latihan Butt Kick Jump Terhadap Peningkatan Daya Ledak Otot Tungkai Pemain Bola Voli Universitas Dehasen Bengkulu - Yupisa P.A; Dwingki M.P; Ajis S (Educative Sportive, 2026)
This study aims to determine the effect of butt kick jump training on increasing the explosive power of Dehasen University Bengkulu volleyball players. Using the total sampling method in determining the number of respondents and obtained 14 respondents volleyball athletes Dehasen University Bengkulu. This experimental study uses the One Group Pre test - Post test design form is a pre-experimental design that contains a pre-test (test before being given treatment) and a post-test (test after being given treatment) in one group. Data collection used is using test scores. Using descriptive data analysis techniques and t-tests. The results of this study indicate that there is an effect of butt kick jumps on increasing the explosive power of Dehasen University Bengkulu volleyball players with a calculated t value = 2.977 while the t table is 1.771 with a significance level of α = 0.05 and dk = 14.